The elegance of prickly sensations - Imambocus, Bibi Nusreen; Soba, Peter (eLife, 2022)
Neurons sensing harmful mechanical forces in the larvae of fruit flies have a striking architecture of dendrites that are optimized to detect pointy objects.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Ca-α1D; D. melanogaster; dendritic morphology; mechanosensation; neuroscience; nociception; Piezo; Ppk1/Ppk26